2016
DOI: 10.1016/j.resinv.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen profiles and molecular epidemiology of respiratory viruses in Japanese inpatients with community-acquired pneumonia

Abstract: Prevalence of respiratory virus infection in CAP inpatients was 22.3%. The detected viruses display high genetic divergence and correlate with increased respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Likewise, it was shown that an infection with Pseudomonas aeruginosa in primary bronchial epithelia cells could aggravate cells' inflammatory response to RV infections [47]. However, there may be a bidirectional influence, as RV infections also seem to promote secondary bacterial infections [2,48], which may be associated with the disruption of the epithelial barrier of the respiratory tract [49]. Thus, the compound effect of having multiple infections could thus enhance the rate of illness and its severity.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, it was shown that an infection with Pseudomonas aeruginosa in primary bronchial epithelia cells could aggravate cells' inflammatory response to RV infections [47]. However, there may be a bidirectional influence, as RV infections also seem to promote secondary bacterial infections [2,48], which may be associated with the disruption of the epithelial barrier of the respiratory tract [49]. Thus, the compound effect of having multiple infections could thus enhance the rate of illness and its severity.…”
Section: Discussionmentioning
confidence: 99%
“…Other respiratory viruses such as influenza viruses, HPIV, and HRV have been reported to cause lower respiratory symptoms and/or community-acquired pneumonia in adults [8] Recently, we reported the prevalence of viral infections in adult asthma attack patients conducted in the same period of this study that the frequency of HRV and RSV infections seemed to be high in autumn, while HMPV was likely to occur in spring, and influenza virus infections were most common in Table 3 Comparison of the clinical findings between IPF and non-IPF ILDs cases. winter and spring [9].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Logistic regression analysis showed that the repeated infection (OR=3.315, P=0.005), multi-resistant bacterial infection (OR=1.915, P=0.008) and D-D (OR=1.936, P=0.009) were independent risk factors for SCAP (P<0.05). This is because Gram-negative bacteria dominate in the infectious bacteria of SCAP, and Pseudomonas aeruginosa is the most common, followed by Klebsiella pneumoniae , Staphylococcus aureus and Staphylococcus epidermidis ( 15 ). With the repeated infection, changes in pathogenic bacteria and increased bacterial resistance in patients, multi-resistant bacterial infection will be caused.…”
Section: Discussionmentioning
confidence: 99%